Computer-aided design and manufacturing for the jewellery industry - Lee, Han Boon. (2009)
Based on a study of the current practices of the local jewellery industry and a survey of their products, attention is focused on automating the prototyping of a large group of jewellery which are usually handcrafted in parts and subsequently joined together to form the final design. Layered manufacturing systems are surveyed to select a suitable one for producing solid jewellery prototypes rapidly. The Stereolithography Apparatus is chosen based on its suitability and availability. By integrating the SLA with a computer aided 3D modelling system, a prototype computer aided jewellery design system is set up in an attempt to ease the design prototyping bottleneck being experienced by the jewellery industry.